The liver, liver metastasis and liver cancer: A special case for immunotherapy with cytokines and immunostimulatory monoclonal antibodies - Mazzolini Rizzo, Guillermo Daniel (2012)
"The immunologic outcome of liver transplantations tells us that this organ is somehow specialized as a tolerogenic organ under steady state conditions."